Total quality management (TQM): Implementation in primary education system of Bangladesh - K. Hasan; Md. S. Islam; A. T. Shams; H. Gupta (International Journal of Research in Industrial Engineering, 2018)
The role of primary education is to ensure the broad-based development of pupils. This means ensuring that all pupils are able to develop their cognitive, social, emotional, cultural, and physical skills to the best of their abilities and preparing them for their further school career. It is known that education in Bangladesh is highly subsided. The government has given the highest importance to the education sector to ensure education for all. A large percentage of a country's national budget is set to promote education and make it more accessible. But the education system of Bangladesh faces several problems. Low performances in primary levels and dropout are matters of concern because the low performances can result of poverty, widening disparities in education opportunities and facilities, poor school attendance, less contact time in school, lack of skilled school teachers, and lack of coordination between parents and the teachers. For that reasons, this research is conducted to implement the Total Quality Management (TQM) to improve the condition and the quality of the primary education system. Total Quality Management is a tool for ensuring proper quality in the entire organization. The main objective of the research is to eliminate problems such as the lack of quality of teachers and to improve the relation between teachers, students, and parents. Another aim of this research is to improve the quality of the environment of the class room in order to motivate the students to go to school; so, the dropout can be reduced.